Data Security in Cloud Computing - Kumar Kishan Chandra; Dr. Manisha Kumari Deep (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This article discusses data security issues in cloud computing. It is the study of data in the cloud and its associated security issues. This article will introduce data protection procedures and global practices to insure that data are protected as much as possible by reducing risks and threats. Keeping data in the cloud has been beneficial for many applications, but it creates risks by exposing data to applications that are already weakly secured. Similarly, if the reliability of the guest process (which may have a vulnerability) is unknown when running on a hypervisor, using cloud computing virtualization can lead to the exposure of dangerous information. The white paper will also provide insights into security information in transit and at rest. Learn all levels based on SaaS (Software as a Service), PaaS (Platform as a Service) and IaaS (Infrastructure as a Service)
Keywords: Data Security; Cloud Computing; Data Protection; Privacy; Risks; Threats